Computation of Errors and Their Analysis on Physics Experiments - Chhetri, Khadka Bahadur (Himalayan Physics, 2013)
The process of evaluating uncertainty associated with a measurement result is often called uncertainty analysis or error analysis. Without proper error analysis, no valid scientific conclusions can be drawn. The uncertainty of a single measurement is limited by the precision and accuracy of the measurement. The errors are communicated in different mathematical operations. Every deviation in result of experiment from the expected one has important significance. Even on undergraduate level of our domestic universities, error analysis and interpretation of the result should be done instead of writing just the points of precautions. This approach will make the students somewhat familiar about the error analysis on advanced level. Otherwise, the hesitation and difficulty about error analysis which stuns M.Sc. level beginner student will persist and the necessity of standardization of our lab reports will remain untouched for next several years also. The Himalayan Physics Vol. 3, No. 3, July 2012 Page: 78-86